Lesson Learned from Yangon to Mandalay on Wastewater Treatment Systems: 10.32526/ennrj/21/20230083 - Swan, Kaung Htet; Surinkul, Nawatch; Prapaspongsa, Trakarn; Boontanon, Suwanna; Thongdara, Romanee (Environment and Natural Resources Journal, 2023)
This paper presents a comparative analysis of wastewater management practices in Myanmar’s major cities, Yangon and Mandalay, with a focus on drawing valuable lessons from Yangon’s experiences and proposing recommendations for the improvement of Mandalay’s domestic wastewater management, drawing insights from a SWOT analysis. Both cities are facing challenges due to rapid urbanization, leading to untreated discharge into the environment. The study identifies common challenges in both Yangon and Mandalay, such as limited treatment capacity, environmental concerns, and funding gaps. The decentralized-centralized strategy is a successful approach for Yangon even though the capacity is not high. Results showed that 17.5% of Decentralized Wastewater Treatment Systems (DEWATS) users were highly satisfied and 45% were somewhat satisfied. Yangon’s experience with centralized systems showed that it took several years to cover the entire city for treatment, resulting in issues to cover revenue expenditures. If Mandalay adopts a similar, it will likely encounter the same issues. A recommended approach would be to implement an integrated system with DEWATS, which offers a better solution. The recommendations for sustainable wastewater management in Mandalay include active stakeholders’ involvement in decision-making, promoting community participation, and providing training. Transparency and shared responsibility are crucial for success. Addressing membrane fouling, sludge disposal, and implementing monthly fees are essential for sustainable implementation. An integrated approach along with environmental and social impact assessments are necessary to develop a cost-effective and efficient wastewater treatment system while safeguarding public health and the environment. These insights offer broader implications, guiding developing countries towards more effective and environmentally responsible wastewater management practices.